A case of Fitz-Hugh-Curtis syndrome diagnosed by noninvasive metagenomic next-generation sequencing - Ding, Chengcheng; Chen, Run; Guo, Peng; Yang, Juhua; He, Mian (Taiwanese journal of obstetrics & gynecology, 2024)
Fitz-Hugh-Curtis Syndrome (FHCS) is an inflammation of the liver capsule as a complication of pelvic inflammatory disease (PID) in sexually active women, mostly associated with Chlamydia trachomatis (C. trachomatis) and Neisseria gonorrhoeae. Classically presenting as sharp right upper quadrant pain, usually accompanied salpingitis and ascites. With nonspecific clinical presentation and poor specificity, definitive diagnosis needs tissue biopsy and culture by laparoscopy. We report the case of a 22-year-old female with a 2-month history of abdominal pain and distention. Symptomatic relief when supportive treatments were given, with the ultrasound and PET-CT suggested advanced bilateral ovarian cancer. After metagenomic next-generation sequencing (mNGS) detected C. trachomatis in ascitic fluid. Following anti-infective medication, clinical improvement was satisfactory and the patient was discharged. FHCS with distention was rare and challenging to diagnose. The mNGS would be a potent, non-invasive pathogen detection method with significant sensitivity and specificity.